2013
DOI: 10.1111/jce.12278
|View full text |Cite
|
Sign up to set email alerts
|

Speech‐Induced Atrial Tachycardia: An Unusual Presentation of Supraventricular Tachycardia

Abstract: A 63-year-old male radio announcer was admitted with a narrow complex, long RP tachycardia. While in the awake state, the patient spoke in his radio voice, initiating and maintaining the tachycardia. Three-dimensional electroanatomic mapping during electrophysiology study localized the tachycardia to the ostium of the right superior pulmonary vein. After single radiofrequency energy application, no further arrhythmias were inducible with speech. At more than 1 year of follow-up, the patient had no recurrences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Speech-induced AT is rare, and only sporadic cases were reported. [2][3][4] However, the underlying mechanism is unclear. In our case, we found that an increase in LAP preceded the episode of AT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Speech-induced AT is rare, and only sporadic cases were reported. [2][3][4] However, the underlying mechanism is unclear. In our case, we found that an increase in LAP preceded the episode of AT.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, similar viewpoints have been revealed by a few previous reports. [2][3][4] Nevertheless, the exact mechanism of speech-induced AT remains to be elucidated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AT and AF have been reported with coughing, speaking, and swallowing 2, 3, 4, 5, 6, 7. One case localized the site of earliest activation to the roof of the left atrium, whereas another noted earliest activation was in the anteroseptum of the left atrium 2, 3.…”
Section: Discussionmentioning
confidence: 99%
“…AT and AF have been reported with coughing, speaking, and swallowing. 2 , 3 , 4 , 5 , 6 , 7 One case localized the site of earliest activation to the roof of the left atrium, whereas another noted earliest activation was in the anteroseptum of the left atrium. 2 , 3 Fan et al 2 postulated that it may be due to an anomalous efferent input from the recurrent laryngeal nerve to the left atrial ganglionic plexuses.…”
Section: Discussionmentioning
confidence: 99%